Evaluation of Junior High School Students' Mathematics Learning Using the APIPA Evaluation Model (Assessment, Planning, Implementation, Product, And Appreciation) - Syahrir, Syahrir; Sumiadi, Raden; Fandir, A. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to evaluate junior high school (SMP) students' mathematics learning using the APIPA (Assessment, Planning, Implementation, Product, and Appreciation) evaluation model. The APIPA model is used as a comprehensive evaluation framework to assess the quality of mathematics learning processes and outcomes. This study used a quantitative approach with a survey method of 157 junior high school student respondents in North Lombok Regency, Indonesia. Data were collected using a Likert-scale questionnaire instrument and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach through the SmartPLS application. The results showed that all stages of the APIPA model had a positive and significant effect on the quality of junior high school students' mathematics learning. Thus, the APIPA model is considered effective and relevant as an evaluation model for mathematics learning at the junior high school level